2009
DOI: 10.1017/s0266467409990125
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of epiphytes to the abundance and species richness of canopy insects in a Mexican coffee plantation

Abstract: Abstract:The abundance of epiphytes has been assumed to be important in explaining the high diversity of tropical canopy arthropods. In this study we assessed the possible role that the presence of epiphytes may have on the diversity and abundance of canopy insects in an experimental study conducted in a coffee plantation in Coatepec, Veracruz, Mexico. Epiphytes were removed from trees in one of two plots in two sites of the coffee plantation. In each plot we collected insects from three Inga jinicuil trees by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 60 publications
2
33
0
1
Order By: Relevance
“…The study area is located in southeast Xalapa, Veracruz, Mexico. The site is a 40‐year‐old shade‐coffee plantation called “La Orduña” (19°28′02″N, 96°55′45″W), a well‐known site for the study of species diversity (Cruz‐Angón et al., ; Manson, Hernández‐Ortiz, Gallina, & Mehltreter, ). We selected three trees of the dominant species Inga jinicuil G. Don (Mimosaceae), which harbours the greatest diversity of epiphytes (more than 40 species; Cruz‐Angón et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The study area is located in southeast Xalapa, Veracruz, Mexico. The site is a 40‐year‐old shade‐coffee plantation called “La Orduña” (19°28′02″N, 96°55′45″W), a well‐known site for the study of species diversity (Cruz‐Angón et al., ; Manson, Hernández‐Ortiz, Gallina, & Mehltreter, ). We selected three trees of the dominant species Inga jinicuil G. Don (Mimosaceae), which harbours the greatest diversity of epiphytes (more than 40 species; Cruz‐Angón et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…To what extent, and at what rates, are compounds generated from epiphyte microbial communities or leached from the epiphyte itself, re-assimilated by within-canopy ecosystems (especially after prolonged dry periods like those studied by Coxson (1991) and Coxson et al (1992))? In our efforts to better understand the final chemical composition of net precipitation fluxes to soils, we should not neglect the important within-canopy biogeochemical functions reliant on throughfall and stemflow en route to the surface that support the biodiversity of microbe, plant, vertebrate and invertebrate communities across scales, from the individual epiphyte (Carrias et al, 2012), to the single tree canopy (Nieder et al, 2001;Cruz-Agnón et al, 2009), and even the forest canopy scale (CruzAgnón and Greenberg, 2005).…”
Section: Solute Lichen Bryophyte Vascular Studiesmentioning
confidence: 99%
“…G. lucida and its associated epiphytic communities provide habitat, nectar, water, fruits and nesting materials for invertebrates and birds (Nadkarni 1989;Benzing 1990;Gentry 1991;Nadkarni 1992;Affeld 2008;Cruz-Ango´n et al 2009). Affeld (2008) found 397 invertebrate species in a survey of 120 epiphytic assemblages in forests of the west coast of the South Island, while O'Donnell & Dilks (1994) found that up to 9% of observed feeding by birds in south Westland was on epiphytes.…”
Section: Other Biotic and Abiotic Relationshipsmentioning
confidence: 99%